(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The main theme is the pursuit of control over one’s destiny. Manju Kapur represents the middle class and has even drawn similarities to Jane Austen because of her perceptive, ultimately sympathetic character representations of people in perilous circumstances. In his third book, HOME, Kapur skillfully interweaves "conflicting loyalties, intrigues, triumph" along with the "small rebellions and intense power struggle" that characterise the common human experience. The Sunday Times described Manju Kapur’s third book, Home, as "glistering with detail and emotional acuity." This book was included on the Hutch crossword prize shortlist. The narrative of a family living in the hustle and bustle of the Banwari Lal cloth shop is fascinating. The home, which is used in both its physical and metaphysical manifestations, is the main subject of the work. In her books, Manju Kapur has always attempted to paint a more nuanced image of women’s struggles.